UNCTAD commodity yearbook - United Nations Conference on Trade and Development (New York : United Nations, 1986)
This monograph is a published by the United Nation to improve product coverage and develop analytical tables that will be of practical use to government, researchers, international organization and research institute with interest in international commodity policy issues
gp. 25/01/2019
Loan
Keywords: Händel; Primary commodities; Commercial products; Productie; Consumptie; Commercial products; Primary commodities